Viral pancreatitis: research advances and mechanisms - Yu, Xianqiang; Wang, Minchao; Kong, Qingming (Frontiers in Microbiology, 2024)
Acute pancreatitis is caused by trypsinogen activation in acinar cells caused by various injury forms (gallstone, high triglycerides, alcohol, etc.). Viral pancreatitis is a clinically rare disease type, which is easily neglected by clinicians and causes serious adverse consequences. Viral pancreatitis involves the entry of viruses into pancreatic cells, triggering inflammation, immune response activation, and enzymatic autodigestion, leading to tissue damage and potential complications. At present, there are few available reports on viral pancreatitis, most of which are case reports. This review brings attention to clinicians by describing the incidence of viral pancreatitis to enhance clinical understanding and patient care.